1993
DOI: 10.1002/pro.5560020309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sequence conservation and three‐dimensional structure in a large family of esterases, lipases, and related proteins

Abstract: Based on the recently determined X-ray structures of Torpedo californica acetylcholinesterase and Geotrichum candidum lipase and on their three-dimensional superposition, an improved alignment of a collection of 32 related amino acid sequences of other esterases, lipases, and related proteins was obtained. On the basis of this alignment, 24 residues are found to be invariant in 29 sequences of hydrolytic enzymes, and an additional 49 are well conserved. The conservation in the three remaining sequences is some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
358
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(372 citation statements)
references
References 66 publications
11
358
0
3
Order By: Relevance
“…Although its functional domains remain uncharacterized, ASPA has been referred to as a member of the α/β-hydrolase superfamily of enzymes because of its enzymatic inhibition by diisopropyl fluorophosphates, which suggests a catalytic serine, and because of its local sequence homology to catalytic cores in esterases (Cygler et al 1993,Matalon & Michals-Matalon 1999. However, ASPA lacks an invariant serine, a candidate for a catalytic residue, and an alignment study revealed minimal homology of ASPA with serine proteases (Makarova & Grishin 1999,Cygler et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its functional domains remain uncharacterized, ASPA has been referred to as a member of the α/β-hydrolase superfamily of enzymes because of its enzymatic inhibition by diisopropyl fluorophosphates, which suggests a catalytic serine, and because of its local sequence homology to catalytic cores in esterases (Cygler et al 1993,Matalon & Michals-Matalon 1999. However, ASPA lacks an invariant serine, a candidate for a catalytic residue, and an alignment study revealed minimal homology of ASPA with serine proteases (Makarova & Grishin 1999,Cygler et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, ASPA lacks an invariant serine, a candidate for a catalytic residue, and an alignment study revealed minimal homology of ASPA with serine proteases (Makarova & Grishin 1999,Cygler et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…38 TcAChE is homologous to several lipases and esterases, resulting in similar threedimensional structures for all of them. 39 However, this folding pattern (a β-sheet surrounded by α-helices) is also found in hydrolases that bear no similarity to TcAChE or among themselves. This fold, first identified in the 1990's, is designated α/β hydrolase.…”
Section: Ache Structurementioning
confidence: 98%
“…40 It is believed that, in TcAChE, this folding is kept by four salt bridges. 39 Indepth descriptions of structural details and disulfide-linkage patterns, as well as comparisons with structures of other enzymes, can be found elsewhere. 24,28,38,39 …”
Section: Ache Structurementioning
confidence: 99%
“…[1][2][3] They are responsible for the hydrolysis of numerous exogenous and endogenous ester-containing compounds 4,5 and have become of increased interest due to their utility in the activation of prodrugs and metabolism of softdrugs, 6 including the chemotherapeutic agent CPT-11 7 and the anti-influenza viral agent oseltamivir 8 . CaEs are also important in agrochemical research because they detoxify pyrethroid, organophosphate and carbamate insecticides.…”
Section: Introductionmentioning
confidence: 99%